A Shoot Phenological Study of Certain Phyllostachys Bamboo Taxa Under Central European Climatic Conditions - Khin Nyein Chan; Anikó Veres; Zhiwei Liang; Szilvia Kisvarga; András Neményi (Plants)
This study aimed to understand the phenological changes in the shoots of temperate bamboo Phyllostachys spp. grown in Hungary, with a focus on how these changes were influenced by local climatic conditions. Data collected over two years on shoot phenology were analyzed with weather variables, especially air temperature and soil temperature. Shoot emergence date, shoot numbers, and shooting period were recorded within and between Phyllostachys spp. The date of shooting was observed between May and July, and species started shooting in May the most, followed by June. Only one species, P. sulphurea, started shoot emergence in July. Shoot emergence started earlier in 2022 than in 2023 and ranged from 3 days to 27 days. Bamboo shoot phenology was strongly influenced by the air temperature and soil temperature each year. According to our regression analysis, the dates of shoot emergence were influenced by air temperature (r2 = 0.819) in 2022 and 2023 (r2 = 0.781), and soil temperature also influenced shoot emergence (r2 = 0.956) in 2022 and 2023 (r2 = 0.769). Sharp air temperature changes between the shooting season and the period before shooting were considered as the reasons for early shooting. The soil temperature in April before the start of shoot emergence was 8.15 °C, increasing to 14.1 °C during shooting time in May. Abrupt fluctuations of air temperature between the shoot emergence season and the month prior to shooting commencement determined early shooting or late shooting. The soil temperature had to reach 9 °C or above prior to shooting time, as this was found to be a critical temperature for shoot emergence in Phyllostachys bamboo taxa.